REKONSTRUKSI HUKUM AGRARIA GUNA MENUNJANG OTONOMI DAERAH - Tri Handayani; Wachyuni Wachyuni (Universitas Wahid Hasyim, 2008)
The Enactmen of regional autonomy for the Huge lang territory to the district Area is basycally stated as the claim of reformation. It also become the main clue for the regional autonomy. Both of them were endorsed in the Basic Principle of Agrarian Law (UUPA). The land territory in the whole nation was revealead and endorsed in the form of justice to the society in this regulation. It also have another main purpose a for the growth of prosperity. But in fac, thee the condition of land territory is being far from the basic purpose and claim. The question now is all about the eficiency of Basic Principle of Agrarian Law to hold the regional autonomy.